2012
DOI: 10.4236/ars.2012.13007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Small Wetlands with Multi Sensor Data in East Africa

Abstract: The dynamic nature and inaccessibility of wetland ecosystems restricts in situ data collection and promote the use of various remote sensing platforms. This is because of their ability to record large areas in comparatively short time periods and map physically unreachable areas. Sensors in the optical and microwave range of the electromagnetic spectrum play a critical role in wetlands detection and delineation, as they complement each other in data collection. This study examined the potential of optical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Clustering represents a common method to perform image segmentation under consideration of multi-spectral and multi-temporal data [63]. Cluster algorithms have already been used as segmentation methods for the derivation of TFV [64][65][66]. The grouping of pixels into segments was implemented for the study area using a k-means cluster algorithm.…”
Section: Clustering Approach For Segment Generationmentioning
confidence: 99%
“…Clustering represents a common method to perform image segmentation under consideration of multi-spectral and multi-temporal data [63]. Cluster algorithms have already been used as segmentation methods for the derivation of TFV [64][65][66]. The grouping of pixels into segments was implemented for the study area using a k-means cluster algorithm.…”
Section: Clustering Approach For Segment Generationmentioning
confidence: 99%
“…Both automated and semi-automated techniques were used to map the wetland [12], where Landsat TM bands 3, 4, and 5 were used for image enhancement [8]. Using July 2015 image data, unsupervised image clustering was conducted using the iterative self-organizing data analysis (ISODATA) algorithm [23]; after which, a number of natural clusters were generated following 100 iterations in a self-organizing way [18].…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…It has been shown that satellite remote sensing has the potential to effectively assist in monitoring and inventorying wetlands due to repeated coverages, allowing both seasonal and annual assessments [8,10,11]. Optical remote sensing works effectively in the detection of wetlands [12] and has been used to map large wetland ecosystems, including marshes and swamps on Sango Bay in Uganda [13]. Satellite remote sensing has the capability to identify areas where changes are occurring and where more detailed information must be gathered.…”
Section: Introductionmentioning
confidence: 99%
“…Although wetland extraction has been moderately successful in some applications, automatic mapping remains a challenge, largely due to the ambiguous spectral characteristics and complex shapes, sizes, and forms of wetlands [10,47,48]. In order to assess the change characteristics and dynamics of wetlands in the Yellow River Delta over the past four decades, we proposed a per-parcel level classification approach based on the knowledge transfer classification and machine learning for automatic classification of wetlands.…”
Section: Study Areamentioning
confidence: 99%